The Transcendence of the Social: Durkheim, Weismann, and the Purification of Sociology - Meloni, Maurizio (Frontiers in Sociology, 2016)
Building on Fox Keller’s acute genealogy of the nature–nurture opposition as located in a certain specific social, cultural, and political history in the late nineteenth century (2010), in this paper, I address a parallel problem: the making of a really modern (i.e., non-biological) sociology nearly at the same time as the “hard disjunction” (Keller, 2010) between heredity and the environment, nature and nurture, was made. I argue rather provocatively that traces of borrowing from hard heredity to sociology can be seen in Durkheim’s strategic usage of Weismann to destroy Lamarckian sociology. The transcendence of the social in Durkheim is entirely isomorphic to Weismann’s transcendence of the germ plasm: in both cases, they aimed to construct objective realities, radically independent and exterior from individual tendencies and peculiarities. Weismann offered Durkheim an important scientific companion to make boundaries between sociology and biology. In a Latourian sense (Latour, 1993), the purification strategy of Durkheim was actually helped by a hybridization with Weismann’s biology. In conclusion, by taking Weismann as an anticipator of the genetics revolution a few years later, I argue for a profound complicity between twentieth century non-biological sociology and genetics. They both made space for a neat distinction between biological heredity and sociocultural transmission, heredity, and heritage. If sociology and genetics thought of themselves as rivals and even enemies in explaining social facts, they should reconsider their positions.